PERLINDUNGAN HUKUM NASABAH PENGGUNA MOBILE BANKING - Agung Budiarto; ' Pujiyono (Jurnal Privat Law, 2021)
AbstractThis article aims to determine the regulation and implementation of legal protection obtained by bank customers using mobile banking services. This article belongs to the type of empirical and descriptive legal research. Legal protection regulations for mobile banking customers are based on applicable regulations. The implementation of legal protection for mobile banking users is based on repressive legal protection and preventive legal protection. However, along with the development of technology and information, crimes against technology and information are also developing. Implementation and regulation of legal protection for mobile banking customers need to be reviewed.Keywords: legal protection; mobile banking; customer AbstrakArtikel ini bertujuan untuk mengetahui peraturan dan pelaksanaan perlindungan hukum yang diperoleh nasabah bank pengguna layanan mobile banking. Artikel ini termasuk ke dalam jenis penelitian hukum empiris dan bersifat deskriptif. Peraturan perlindungan hukum untuk nasabah mobile banking didasarkan pada peraturan yang berlaku. Pelaksanaan perlindungan hukum bagi nasabah pengguna mobile banking didasarkan pada perlindungan hukum represif dan perlindungan hukum preventif. Namun, seiring dengan perkembangan teknologi dan informasi, kejahatan terhadap teknologi dan informasi juga berkembang. Peraturan dan pelaksanaan perlindungan hukum untuk nasabah pengguna mobile banking perlu ditinjau kembali.Kata Kunci: perlindungan hukum; mobile banking; nasabah